An economic study on the cost and return of garlic crop production in Lattakia Governorate (Al-Hafa area as a model) - سرحيل زياد (Latakia University Journal -Biological Sciences Series, 2023)
The research was carried out in the Al-Haffah region of Latakia Governorate for the agricultural season (2022-2023), due to the importance of cultivating the garlic crop in this region, on a sample of 20 garlic farmers in the Al-Haffa region, the size of which was calculated by taking 20% of the total population. The studied area, given that it is a homogeneous area in terms of geographical, social, economic and productive conditions, and the main objective of the research is to study the reality of garlic cultivation in Syria in general and in Lattakia Governorate in particular, in addition to the descriptive economic analysis of the costs and revenues of garlic production in the Al-Haffa area of Lattakia Governorate, and the study and analysis of indicators In terms of economic efficiency, the primary field data were collected through a personal interview with farmers, based on a form specially prepared for the purpose of the research. As a result of the study, the average annual net profit achieved from a dunum planted with garlic was 2079529 SP / dunum / year, while the profitability coefficient compared to invested capital reached 81.5%, and compared to production costs 98%, and it is considered a very good indicator in the field of agricultural investment, as it The profitability rate is equivalent to about 98 SP for every 100 Syrian pounds invested annually, and the variable asset turnover rate was 2.2, which is evidence of efficient investment of available resources and increased productivity. The results also showed that the economic efficiency index reached 1.98, which is greater than the correct one. , which indicates the efficient use of fixed and variable capital in a good and ideal way, and the feasibility of producing the garlic crop in the Al-Haffah region. The research concluded that it is necessary to increase interest in garlic cultivation, while encouraging and motivating farmers to increase the areas cultivated with this crop, given the economic savings achieved for rural families, diversifying sources of income, and improving their standard of living.